ANALISIS PERAN PERKEMBANGAN KOGNITIF ANAK DALAM KEMAMPUAN MEMBACA DI SEKOLAH DASAR - Dwi Novita Sari; Ichsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reading ability is a fundamental skill that significantly influences students’ academic success at the elementary level. However, many third-grade students still struggle with deep reading comprehension, especially in answering inferential questions. This study aims to analyze the role of cognitive development in elementary students’ reading abilities. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation at a public elementary school in Palembang. The findings indicate that while students have mastered technical reading skills, they remain weak in understanding abstract reading content. Teachers have applied strategies such as read-aloud sessions, discussions, and visual media as forms of scaffolding to support students’ comprehension. The challenges encountered include limited instructional time, large class sizes, and a lack of reading materials suited to children's cognitive stages. These results highlight the importance of designing reading instruction that aligns with students’ cognitive development stages to improve their ability to understand texts comprehensively and meaningfully.